The GSK3/Shaggy-Like Kinase ASKα Contributes to Pattern-Triggered Immunity - Stampfl, Hansjörg (Plant Physiol, 2016)
The first layer of immunity against pathogenic microbes relies on the detection of conserved pathogen-associated molecular patterns (PAMPs) that are recognized by pattern recognition receptors (PRRs) to activate pattern-triggered immunity (PTI). Despite the increasing knowledge of early PTI signaling mediated by PRRs and their associated proteins, many downstream signaling components remain elusive. Here, we identify the Arabidopsis (Arabidopsis thaliana) GLYCOGEN SYNTHASE KINASE3 (GSK3)/Shaggy-like kinase ASKα as a positive regulator of plant immune signaling. The perception of several unrelated PAMPs rapidly induced ASKα kinase activity. Loss of ASKα attenuated, whereas its overexpression enhanced, diverse PTI responses, ultimately affecting susceptibility to the bacterial pathogen Pseudomonas syringae. Glucose-6-phosphate dehydrogenase (G6PD), the key enzyme of the oxidative pentose phosphate pathway, provides reducing equivalents important for defense responses and is a direct target of ASKα. ASKα phosphorylates cytosolic G6PD6 on an evolutionarily conserved threonine residue, thereby stimulating its activity. Plants deficient for or overexpressing G6PD6 showed a modified immune response, and the insensitivity of g6pd6 mutant plants to PAMP-induced growth inhibition was complemented by a phosphomimetic but not by a phosphonegative G6PD6 version. Overall, our data provide evidence that ASKα and G6PD6 constitute an immune signaling module downstream of PRRs, linking protein phosphorylation cascades to metabolic regulation.